Highly conductive templated-graphene fabrics for lightweight, flexible and foldable supercapacitors. (10th July 2017) - Zhang, Ping; Zhang, Hanzhi; Yan, Casey; Zheng, Zijian; Yu, You
Abstract: The templated-rGO fabric, featuring high conductivity (<1.0 Ω □ −1 ) and low density (160 mg cm −2 ), is prepared by a simple dip-coating technique with sequentially coating nickel via polymer-assisted metal deposition (PAMD) and reduced-graphene oxide (rGO) on textile fabric templates at very mild conditions and is used in the fabrication of energy storage devices. As a proof of concept, both the layered and planar supercapacitors (SCs) are successfully fabricated using the rGO fabrics as templates, and both exhibit excellent electrochemical performance, ultrahigh stability with 2000 charge–discharge cycles and mechanical flexibility at bending ( r   =  3 mm) and even folding states. It is found that the material of textile fabric used has a profound effect on the electrochemical property of SCs. The comparison result reveals that loose natural cotton fabrics are more suitable than tight man-made nylon fabrics for preparing high-performance SCs. In addition, such supercapacitor can be sewed into commercial textiles and powers a LED light, indicating promising applications in wearable electronics.